Students’ Habit in Watching English Movies and Its Correlation with their English Listening Skills - Rachmi, Femalinda Anindita; Sari, Mariska Intan (Universitas Muhammadiyah Yogyakarta, 2022)
Improving listening skills can be done from various learning media; one of them is movies. Movies provide audio and visual, making students convey the meaning of the language while watching. One of the most difficult skills to master is listening. In order to have better skills in listening, students need learning media to improve their listening skills. This study aimed to examine the students' habit in watching English Movies at an English Language Education Department (ELED) of a Private Islamic University in Yogyakarta, the students' listening skill at the ELED of a Private Islamic University in Yogyakarta, and the correlation between the students’ habit in watching English movies and their listening skills. This research was conducted at an ELED of a Private Islamic University in Yogyakarta. Quantitative approach with correlational design was employed in this study. The study included 185 ELED Batch 2018 students and used a convenience sample technique. A questionnaire and the listening TOEFL test score were used to collect the data. The Pearson Product Moment Correlation test was used to compute and analyze the scores from both data, and SPSS v.26 was used to perform the correlation. Moreover, the result revealed that probability value was 0.389 which means that the probability value is higher than 0.05 (0.389>0.05) and it implied that alternative hypothesis was rejected. It means that there was no significant correlation between the two variables, the students’ habit in watching English movies and their listening skills. It can be inferred that if the students have a good habit in watching English movies, it does not mean that their listening skills are also good